(untitled) (Journal of Parents and Teachers, 1996)
The artistic representation is not an exact reflection of reality, but a personal interpretation of the artist. Aesthetic resources such as color shades, type of photography and camera movements, which contribute to the expression of the image, are mentioned. In addition, the advertising spot is considered as a message that acts as a sender to a specific receiver.